AUF DIE PERSÖNLICHKEIT DES LEHRERS KOMMT ALLES AN – FORSCHUNGSBERICHT ZUM PROFIL EINES „GUTEN” FREMDSPRACHENLEHRERS IN ALLEN SCHULTYPEN IN POLEN / IT ALL DEPENDS ON THE TEACHER’S PERSONALITY – PROFILE OF A ‘GOOD’ FOREIGN LANGUAGE TEACHER IN ALL TYPES OF SCHOOLS IN POLAND – RESEARCH REPORT - Krystyna Mihułka; Joanna Chojnacka-Gärtner (Journal of Languages for Specific Purposes, 2019)
Since the 1960s, there has been increasing interest in the teacher’s professional qualifications in didactics, leading in some ways to the ‘dehumanization’ of the teacher. And yet it is the teacher’s personality that often determines his/her educational and didactic influence on the students. The aim of this article is to present a portrait of the so-called good foreign language teacher, which has been created on the basis of the comments made by about 840 Polish students of modern languages, and pupils representing various types of schools (from primary schools, through middle and secondary schools, to colleges and universities) in two voivodeships of Poland, namely Podkarpackie Voivodeship and Wielkopolska Voivodeship. In this picture, teacher personality traits, the majority of which are regarded as values not only in professional life (e.g. in the teaching profession), but also in personal life, have ranked the highest. Personality traits have overshadowed the other two groups of qualities, which foreign language teachers are also equipped with, i.e. didactic and glottodidactic ones. On the basis of the results of our research, it can be stated that the respondents (regardless of the educational stage) are inclined to perceive the (foreign language) teacher mostly as a good man, and not as a programmed robot, possessing a wide range of skills and competences. The respondents’ beliefs are, therefore, closer to the psychologists’ and pedagogues’ beliefs from the first half of the twentieth century than to contemporary concepts, in which a ‘good teacher’ is characterized as possessing only an appropriate, specialized education.